2024
DOI: 10.1002/pro.4956
|View full text |Cite
|
Sign up to set email alerts
|

Copper ion incorporation in α‐synuclein amyloids

Gulshan Walke,
Ranjeet Kumar,
Pernilla Wittung‐Stafshede

Abstract: Copper ion dys‐homeostasis is linked to neurodegenerative diseases involving amyloid formation. Even if many amyloidogenic proteins can bind copper ions as monomers, little is known about copper interactions with the resulting amyloid fibers. Here, we investigate copper interactions with α‐synuclein, the amyloid‐forming protein in Parkinson's disease. Copper (Cu(II)) binds tightly to monomeric α‐synuclein in vitro involving the N‐terminal amine and the side chain of His50. Using purified protein and biophysica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Recently, in vitro studies showed that copper could bind to pre-formed and formed AS fibrils and affect the morphologies [ 33 ]. Yet, the effect of copper on the early-stage oligomers and morphologies at the atomic resolution are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in vitro studies showed that copper could bind to pre-formed and formed AS fibrils and affect the morphologies [ 33 ]. Yet, the effect of copper on the early-stage oligomers and morphologies at the atomic resolution are still unknown.…”
Section: Introductionmentioning
confidence: 99%